Analyzing the Litigation Practice Concerned with the Consideration of Intellectual Property Cases in Kazakhstan - DEMEZHANOVA, Saule M.; KAUDYROV, Tolesh E.; DEMIDOVA, Galina S. (Journal of Advanced Research in Law and Economics, 2019)
Nowadays, one of the pressing issues of intellectual property protection is unsystematic judicial enforcement. It is a common situation when different courts hold diametrically opposite positions in similar cases. Moreover, court decisions do not always comply with the existing law and litigation practice in intellectual property cases, which ultimately hinders the uniform and accurate application of the law in this sphere. In addition, the effectiveness of intellectual property rights significantly reduces due to the adoption of ‘ridiculous’ judicial acts, which negatively affects the policy pursued by Kazakhstan to fight against the violation of the above-mentioned rights. The article is relevant since the problem in question is insufficiently studied, which conditions scientific interest and determines its applicability. The main objective of this research is to consider and analyze law enforcement based on the study of civil cases in the sphere of intellectual property, as well as identify contradictions and gaps in the current legislation on intellectual property protection. In this regard, the article aims at identifying the controversial aspects of this category of cases, explaining their causes and offering a possible solution. The article analyzes judgments delivered by courts of the Kostanay Region regarding intellectual property, evaluates the existing legislation on intellectual property rights, reveals topical issues and develops ways of addressing them. The main approach to studying the above-mentioned problem is analysis that helps consider some claims challenging certain intellectual property rights, which is also the research object. Since the litigation practice concerned with intellectual property protection is being developed, this article can predict a possible position of courts on this issue. The theoretical and practical significance of this study is conditioned by the conclusions drawn by the authors regarding the development and improvement of the current civil and civil procedure legislation. Thus, this article is of practical interest not only to students and lecturers within the framework of the ‘Intellectual Property Rights’ discipline, but also to intellectual property owners and judges. The scientific novelty of this study can be explained by the comprehensive approach to analyzing the effective protection of intellectual property rights in modern conditions with due regard to the law enforcement system of Kazakhstan and the need to strengthen the role of the state in solving problems related to the protection of intellectual property rights.